2003
DOI: 10.1038/sj.leu.2402782
|View full text |Cite
|
Sign up to set email alerts
|

The stem cell mobilizing capacity of patients with acute myeloid leukemia in complete remission correlates with relapse risk: results of the EORTC-GIMEMA AML-10 trial

Abstract: Variable numbers of CD34 + cells can be harvested from the blood of AML patients in CR after G-CSF supported mobilization following consolidation chemotherapy. We hypothesized that a decreased ability to mobilize stem cells reflects a chemotherapy-induced reduction in the number of normal and leukemic stem cells. We therefore analyzed whether the mobilizing capacity of these patients was of prognostic significance. 342 AML-patients in first CR received daily G-CSF from day 20 of the consolidation course and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
2
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 12 publications
1
57
2
1
Order By: Relevance
“…The total number of CD34+ cells collected during all subsequent mobilization rounds could not be used for this purpose as this was influenced by the predetermined target of 2 × 10 6 CD34+ cells/kg (Table 3). Previously, 17 we analyzed the DFS according to the number of collected CD34+ cells, irrespective of the treatment administered to the patient. In the present study, we compared the outcome (DFS and DFI) in both treatment arms: APBSCT vs ABMT on an intention-to-treat basis after adjustment for the number of CD34+ cells, cytogenetics and number of courses to reach CR, age and treatment to remission-induction treatment (Table 4; for more details, see Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The total number of CD34+ cells collected during all subsequent mobilization rounds could not be used for this purpose as this was influenced by the predetermined target of 2 × 10 6 CD34+ cells/kg (Table 3). Previously, 17 we analyzed the DFS according to the number of collected CD34+ cells, irrespective of the treatment administered to the patient. In the present study, we compared the outcome (DFS and DFI) in both treatment arms: APBSCT vs ABMT on an intention-to-treat basis after adjustment for the number of CD34+ cells, cytogenetics and number of courses to reach CR, age and treatment to remission-induction treatment (Table 4; for more details, see Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…19,20 In an earlier analysis, we showed that the duration of hypoplasia after the consolidation course was short in the group of patients with a high CD34+ cell harvest, probably reflecting an in vitro purging of the normal and leukemic stem cells. 17 A shorter duration of pancytopenia after the consolidation course, and especially the duration of neutropenia, was associated with a worse prognosis. Genetic polymorphisms in the ABCG2 transmembrane transporter protein may contribute to differential survival outcomes in AML patients by a decreased drug efflux and higher cytotoxicity in both normal progenitors and AML cells and a longer hypoplasia after the consolidation course.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no clear evidence to explain this phenomenon, as the incidence of high-risk patients was equally distributed between both arms. Keating et al 4 have reported that the capacity to harvest high numbers of CD34 þ cells can be considered as an independent poor prognosis factor, reflecting a low sensitivity for chemotherapy with less efficient in vivo purging of leukemic stem cells. In this study, most of the patients (75%) in each arm received a graft collected after early intensification, and the capacity of mobilization was indeed significantly higher in arm B.…”
mentioning
confidence: 99%
“…1,2 These data, however, still await confirmation. Further, it is not known if the prognostic value of CD34 þ cell mobilization can be overcome by allogeneic transplantation.…”
Section: Introductionmentioning
confidence: 91%